Design, synthesis and anticonvulsant-analgesic activity of new N-[(phenoxy)alkyl]- and N-[(phenoxy)ethoxyethyl]aminoalkanols12. Issue 1 (30th November 2016) - Rapacz, Anna; Waszkielewicz, Anna M.; Pańczyk, Katarzyna; Pytka, Karolina; Koczurkiewicz, Paulina; Piska, Kamil; Pękala, Elżbieta; Budziszewska, Bogusława; Starek-Świechowicz, Beata; Marona, Henryk
Abstract : New aminoalkanols have been synthesized and evaluated for their anticonvulsant activity in maximal electroshock (MES), maximal electroshock seizure threshold (MEST) and pentylenetetrazol (PTZ) tests, and show promising activity. Abstract : New derivatives of N -[(phenoxy)alkyl]- and N -[(phenoxy)ethoxyethyl]aminoalkanols have been synthesized and evaluated for their anticonvulsant activity in maximal electroshock (MES), maximal electroshock seizure threshold (MEST), and pentylenetetrazol (PTZ) tests. Their neurotoxicity was evaluated via rotarod and chimney tests. The compounds exhibiting the most beneficial activity and protection indices were evaluated for analgesic activity using the formalin test for neurogenic pain. They were also evaluated for their influence on cytotoxic activity using in vitro cellular models (HepG2 and CRL-2534 cell lines). Experiments performed using MTT and neutral red cytotoxicity assays showed that all evaluated compounds were safe for normal, glial cells (astrocytes) and did not induce hepatotoxic effects. Based on the results from the in vitro studies, the safety of the evaluated compounds was inferred. The most promising compound in this research was 1-2-[2-(2, 3-dimethylphenoxy)ethoxy]ethylpiperidin-3-ol hydrochloride. Additionally, in silico metabolism prediction for the compound has been performed.